Action-perception coupling in violinists - Stewart, Lauren; Verdonschot, Rinus G.; Kajihara, Takafumi; Sparks, Joseph (Frontiers in Human Neuroscience, 2013)
The current study investigates auditory-motor coupling in musically trained participants using a Stroop-type task that required the execution of simple finger sequences according to aurally presented number sequences (e.g. ‘2’, ‘4’, ‘5’, ‘3’, ‘1’). Digital remastering was used to manipulate the pitch contour of the number sequences such that they were either congruent or incongruent with respect to the resulting action sequence. Conservatoire-level violinists showed a strong effect of congruency manipulation (increased response time for incongruent versus congruent trials), in comparison to a control group of non-musicians. In experiment 2, this paradigm was used to determine whether pedagogical background would influence this effect in a group of young violinists. Suzuki trained violinists differed significantly from those with no musical background, while traditionally trained violinists did not. The findings extend previous research in this area by demonstrating that obligatory audio-motor coupling is directly related to a musicians’ expertise on their instrument of study and is influenced by pedagogy.